Characteristics of the competitive loads of Polish National Amputee Football Team. Pilot studies - Paweł Kalinowski; Olga Bugaj; Jan M. Konarski; Monika Nowakowska; Katarzyna Kulicka; Andrzej Wieczorek; Agata Konarska (Kazimierz Wielki University, 2018)
Background: Information about competitive loads of amputee soccer players are very limited. This element should be one of the base to prepare appropriate training program according to individual needs of players, as well aims of season. The main aim of this pilot study was to describe the characteristics of selected elements of the internal competitive load of football players after unilateral amputations. Methods: The subject involved a group of 15 Polish National Amp Football (PNAF) players after unilateral amputations of t he upper or lower limbs. The age, height and weight were 27.1±8.4 years, 176.2±7.3 cm, 72.0±14.2 kg, respectively. The information were recorded during match between PNAF Team and representative of Polish Clubs, using Polar Team 2Pro System. The data base was analyzed using standard tools and differences among variables was checked by Wilcoxon test. Results: During whole games value of HRmean was 132.6±10.56 bpm with a range from 87.3±10.6 bpm to 182.3±10.69 bpm and energy expenditure was 612.7±164.86 kcal. General, Values of observed variables were higher in the 2nd part of the match but differences among them was not significance. Conclusion: Characterizing the competitive effort will allow to diagnose and determine the nature of the work to use it as specific requirements of the discipline. It can be expected that these information will contribute to the improvement the training process for AMP Footballers and optimize training of the disabled people.